Substance Consumption in University Students and the Relationship with Self-Esteem and Psychological Well-Being - Liliana Mendes; Levi Leonido; Bruna Soares; Tânia Guimarães; Cátia Romão; Mariana Guerra; Elsa Morgado (Desafio Singular, 2024)
The consumption of psychoactive substances among college students is a topic that has increasingly garnered more media coverage in the literature. However, there remains considerable controversy surrounding this issue. Therefore, the objective of this study is to investigate the relationship between substance use habits (including alcohol, tobacco, and other psychoactive substances) and self-esteem and psychological well-being among college students, with the aim of gaining a deeper understanding of this matter. This study employs a descriptive, cross-sectional, quantitative, correlational, and quasi-experimental design. The sample consists of 460 college students aged between 18 and 66 who have internet access. Among these participants, 299 are biologically female and 158 are biologically male. The research utilized several instruments, including a Sociodemographic Questionnaire, the Psychological Well-Being Manifestation Measurement Scale, and the Rosenberg Self-Esteem Scale. The results indicated no statistically significant differences in terms of self-esteem and psychological well-being based on substance use. However, it was observed that the consumption of other psychoactive substances was significantly higher among male participants compared to female participants.